Investigation of the properties of binders of low water demand in a dry hot climate - Yusupov Xamid Vaxobovich; Pulatova Zukhra Umetovna (Genius Journals, 2023)
The main structural building material of our time is cement concrete. The volume of its global production today exceeds 10 billion m3. With all the variety and complexity of the technological process of producing high-quality concrete, one of the important technological tasks is to assess the quality of the binder component in concrete mixtures.
Keywords: microsilicon; metacaolin; modifiers